2020
DOI: 10.1111/ctr.14022
|View full text |Cite
|
Sign up to set email alerts
|

Financial impact of delayed graft function in kidney transplantation

Abstract: Increased utilization of suboptimal organs in response to organ shortage has resulted in increased incidence of delayed graft function (DGF) after transplantation. Although presumed increased costs associated with DGF are a deterrent to the utilization of these organs, the financial burden of DGF has not been established. We used the Premier Healthcare Database to conduct a retrospective analysis of healthcare resource utilization and costs in kidney transplant patients (n = 12 097) between 1/1/2014 and 12/31/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
(45 reference statements)
1
54
0
Order By: Relevance
“…The data showed that not only the dialysis patients but also those who developed DGF without need of dialysis, stayed longer in hospital and their costs surpassed the government reimbursement for the transplant procedure. In a recent publication by Kim et al 1 , similar results were demonstrated. However, to our knowledge this is the first large analysis of costs for this specific transplant population, in Brazil.…”
Section: Discussionsupporting
confidence: 67%
“…The data showed that not only the dialysis patients but also those who developed DGF without need of dialysis, stayed longer in hospital and their costs surpassed the government reimbursement for the transplant procedure. In a recent publication by Kim et al 1 , similar results were demonstrated. However, to our knowledge this is the first large analysis of costs for this specific transplant population, in Brazil.…”
Section: Discussionsupporting
confidence: 67%
“…The increased cost of transplanting marginal kidneys and the concern for regulatory scrutiny increase reluctance toward accepting these offers, and centers that are undergoing performance evaluations have been shown to decrease utilization and transplant volume. 27,28 Restructuring payment models and regulatory metrics on the basis of post-transplant outcomes to remove these disincentives may improve offer acceptance and access to transplantation. An increased willingness on the part of transplant centers to use organs from less than ideal donors will decrease the current unacceptably high discard of deceased donor kidneys and potentially provide organ procurement organizations with the impetus to become more aggressive in their pursuit of organs for transplantation, thereby increasing overall kidney transplantation rates.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Other strategies may also have a role, such as reducing the negative patient-level consequences of rare early allograft failures and increasing reimbursement to account for the increased initial cost of care when using less-than-ideal organs. 37,38 Strengths of our study include the use of nationwide data and established markers of competition and organ availability. Limitations include the possibility of residual confounding.…”
Section: Discussionmentioning
confidence: 99%